Antihypertensive Drug Use and the Risk of Depression: A Systematic Review and Network Meta-analysis - Li, Ying; Fan, Yuanming; Sun, Yangyang; Alolga, Raphael N.; Xiao, Pingxi; Ma, Gaoxiang (Frontiers in Pharmacology, 2021)
Background: Although numerous cohort studies have reported an association between antihypertensives use and depression, the exact effect of antihypertensives on depression remains unclear. Objective: To clarify the association between antihypertensives use and risk of depression. Methods: We retrieved relevant literature using PubMed database until August 30, 2021. Four main classes of antihypertensives, thus, angiotensin antagonists, beta blockers, calcium channel blockers and diuretics were studied. The incidence of depression was pooled based on a single drug category. Network meta-analyses were conducted to comprehensively assess the effects of the 4 classes of antihypertensives on the risk of depression Results: A total of 9 out of 9,557 studies involving 414,873 subjects were retrieved. The pooled results showed a positive association between the use of calcium channel blockers and symptoms of depression [odds ratio (OR): 1.09, 95% confidence interval (CI) :1.06–1.13], while use of the angiotensin antagonists, beta blockers and diuretics was not associated with risk of depression. Subgroup analysis suggested a significant relationship between beta blockers usage and risk of depression in cohort studies (OR:1.21, 95% CI: 1.16–1.26). The results of network meta-analysis indicated that all other three classes of drugs increased the risk of depression: angiotensin antagonists (OR: 1.30, 95% CI: 1.04–1.63), beta blockers (OR: 1.53, 95% CI: 1.22–1.91), and calcium channel blockers (OR: 1.40, 95% CI: 1.12–1.75), compared with diuretics. Conclusions: In conclusion, our results indicate that the use of angiotensin antagonists, beta blockers and calcium channel blockers are potential risk factors of depression.